P35 The Effect of a Traffic Light Labeling Intervention on Amount of Food Served in a College Dining Hall - Martin, Amy; Vollmer, Rachel L. (Journal of nutrition education and behavior, 2021)
College students may not use the nutrition facts label suggesting changes to the label, such as the Traffic Light Label, are needed to increase user friendliness. To examine the effect of traffic light labels on the amount of food served in a university dining hall in comparison to the control nutrition facts panels. This study utilized a repeated measures observational design with a control and an intervention period each lasting 28 days at a Midwestern midsize, private university. Following the control period (nutrition facts panels), each food was labeled with a single color (red, yellow, or green) based upon its nutritional quality. Number of servings per day by color (dependent variable) was combined for both lunch and dinner during the control and intervention period. To compare the amount served per day of each color during control and intervention, a one-way analysis of variance (ANOVA) was used. Bonferroni post hoc tests were utilized for multiple comparisons. The one-way ANOVA for color and time point was significant (F (5, 150) = 4.75, P < 0.001). Yellow-labeled foods during the intervention (M = 341.89, SD = 275.86) was significantly lower than red-labeled foods during control (M = 654.56, SD = 286.40, P < 0.0001) and intervention (M = 604.91, SD = 295.84, P = 0.008). However, there were no other significant differences between colors and time points. These results suggest that traffic light labels may not be more effective than nutrition facts panels in college dining halls to improve food choices. Specifically, there was no significant difference in number of servings per day in red- and/or green-labeled foods between control and intervention. Furthermore, servings per day of red-labeled foods continued to be significantly greater than yellow-labeled foods during the intervention. Because students may not use nutrition labels to make food choices, college dining halls should consider reformulating recipes to improve healthfulness of options.